2000
DOI: 10.1016/s0022-5223(00)70131-0
|View full text |Cite
|
Sign up to set email alerts
|

Does the degree of cyanosis affect myocardial adenosine triphosphate levels and function in children undergoing surgical procedures for congenital heart disease?

Abstract: The degree of cyanosis adversely affects myocardial adenosine triphosphate, function, and clinical outcome of children who undergo cardiac operation. Children with cyanosis should be identified as a higher risk group that could be targeted for supportive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…For example, in the newborn myocardium, lower preischemic high-energy phosphate and glycogen reserves have been associated with lower ATP levels during ischemia, more rapid development of ischemic contracture, and increased postischemic ventricular dysfunction (10,13,26). In children undergoing congenital cardiac repair, slightly lower levels of preischemic ATP (ϳ4 mol/g dry weight) was also strongly associated with more rapid ATP depletion during ischemia, worse postoperative myocardial function, longer time spent in the intensive care unit (ICU), and longer hospital stays (27). Other investigators have suggested that accumulation of anaerobic end-products during ischemia and not reduced ATP levels is responsible for damage to the myocardium during ischemia and reperfusion (28).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the newborn myocardium, lower preischemic high-energy phosphate and glycogen reserves have been associated with lower ATP levels during ischemia, more rapid development of ischemic contracture, and increased postischemic ventricular dysfunction (10,13,26). In children undergoing congenital cardiac repair, slightly lower levels of preischemic ATP (ϳ4 mol/g dry weight) was also strongly associated with more rapid ATP depletion during ischemia, worse postoperative myocardial function, longer time spent in the intensive care unit (ICU), and longer hospital stays (27). Other investigators have suggested that accumulation of anaerobic end-products during ischemia and not reduced ATP levels is responsible for damage to the myocardium during ischemia and reperfusion (28).…”
Section: Discussionmentioning
confidence: 99%
“…As the chronic hypoxia produces long-term changes in the myocardial metabolism and function, the sudden oxygen reintroduction further exacerbates these effects. The impaired contractility due to hypoxia-induced calcium overload and the loss of high energy phosphates are examples of the pathological events amplified by the reoxygenation [59,60]. In addition, the depletion of endogenous antioxidants that characterize chronic cyanosis cannot counteract the oxygen radical-mediated injury when oxygen is reintroduced [61].…”
Section: Reoxygenation and Reperfusion Injuriesmentioning
confidence: 99%
“…Studies have identified that more rapid depletion of high-energy phosphates in the newborn heart is associated with a more rapid onset of ischemic contracture and increased postischemic ventricular dysfunction (15,24,33). In human infants undergoing cardiac surgery, a rather small difference in ischemic ATP levels (4 mol/g dry weight) was correlated with worse postischemic function, longer time spent in the ICU, and longer hospital stays (33). Other investigators have suggested that accumulation of anaerobic end products and not reduced ATP levels is responsible for damage to the myocardium during ischemia (17).…”
Section: Newborn Lv/rv Metabolic Differencesmentioning
confidence: 99%
“…Should these differences between the LV and RV hold in the clinical setting, this may offer a potential explanation for studies that have reported greater left ventricular postischemic dysfunction in normal newborn hearts and newborn hearts with right-sided pathology (1-3). In addition, caution should be exercised by both experimental and clinical investigators using RV biopsies to assess LV metabolism and function in the pediatric population (33,35), as they may be underestimating the potential risk factors associated with ischemia.…”
Section: Newborn Lv/rv Metabolic Differencesmentioning
confidence: 99%